Portosystemic shunt for variceal esophagogastric bleeding and risk of early re-bleeding. Rationale for involuntary intervention: A single-center observational controlled study - Yu. V. Khoronko; E. V. Kosovtsev; R. V. Korobka; A. E. Sarkisov; E. Yu. Khoronko; I. A. Ashimov; E. V. Tadieva (Кубанский научный медицинский вестник, 2024)
Background. Variceal esophageal-gastric bleeding is considered to be a life-threatening complication of portal hypertension in patients with cirrhosis. In some cases, only portosystemic shunt can serve as a life-saving intervention for the patient.Aim. To justify the forced expediency of transjugular intrahepatic portosystemic shunt (TIPS) in case of ineffective drug and endoscopic hemostasis or a high risk of early recurrence of variceal bleeding.Methods. A single-center observational controlled study was conducted to analyze the results of shunt procedure in 62 patients during the period of 2017–2023. The patients were divided into 2 groups: the main group (n = 32) with patients who underwent “early” shunt procedure in a “salvage” variant (n = 10) with continued bleeding and in a “pre-emptive” variant (n = 22) with a high risk of early recurrence of hemorrhage, and the control group (n = 30) with patients who underwent planned shunt procedure. The value of the portosystemic pressure gradient was calculated by subtracting the value of the pressure in the inferior vena cava recorded at the initial stage of the operation from the value of the initial pressure in the portal vein, measured by direct manometry. The authors compared the dynamics of the portosystemic pressure gradient in the study groups at similar stages of the intervention — initial, after embolization of the veins of portal blood flow to the varix, after shunt stenting. The study involved the analysis of mortality rates (6-week, one-year, for the entire observation period) and complications. Statistica-for-Windows 12.0 (StatSoft®, USA) and Excel (Microsoft, USA) were used to calculate descriptive statistics.Results. Patients of both groups achieved normalization of pressure in the portal vein system and, accordingly, the portosystemic pressure gradient as a result of shunt surgery. Effective portal decompression was confirmed by their significant reduction. In the portal vein, the pressure decreased from 33.84 ± 2.70 to 20.53 ± 1.27 mmHg (t = 4.46; p < 0.001) in the main group and from 32.80 ± 3.07 to 20.10 ± 1.60 mmHg (t = 3.67; p < 0.001) in the control group. The dynamics of the portosystemic pressure gradient showed a significant decrease from 26.16 ± 2.69 to 10.06 ± 0.88 mm Hg (t = 5.69; p < 0.001) in the main group, and from 24.83 ± 2.73 to 9.67 ± 1.21 mm Hg (t = 5.08; p < 0.001) in the control group. Together with embolization of the vessels of the hepatofugal inflow of portal blood to the varices, this led to a stable and long-term cessation of variceal bleeding. When comparing the results of shunt procedure in the study groups, no significant differences were found in terms of differentiated mortality rates and complications in both the early and long-term periods. In the main group, the 6-week and one-year mortality rates accounted for 6.3% (n = 2) and 15.6% (n = 5), in the control group — 6.7% (n = 2) and 13.3% (n = 4), respectively (p = 0.917). Mortality in the main group comprised 25.0% (n = 8) over 58 months, in the control group — 23.3% (n = 7) over 60 months (p = 0.886).Conclusion. The transjugular shunt provides a significant reduction in the portosystemic pressure gradient. “Salvage” and “pre-emptive” shunt options can prevent death and early recurrence of bleeding. Their effectiveness increases due to endovascular blockage of vessels that ensures the overflow of esophagogastric varices with portal blood.